2018
DOI: 10.1002/jclp.22695
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and progressive muscle relaxation as standardized session‐introduction in individual therapy: A randomized controlled trial

Abstract: ObjectiveThere is scarce research on the effects of mindfulness in individual therapy. As many practitioners integrate mindfulness exercises into individual therapy, empirical evidence is of high clinical relevance.MethodWe investigated the effects of a session‐introducing intervention with mindfulness elements (SIIME) in a randomized, controlled design. The effects of SIIME on therapeutic alliance and symptomatic outcome were compared with progressive muscle relaxation (PMR) and treatment‐as‐usual (TAU) contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 85 publications
1
45
0
1
Order By: Relevance
“…Hence, the differences between mindfulness and PMR turned out in a more pronounced manner for therapists. In summary, it is important to note that in the main study, the primary outcomes on symptom reduction showed no significant differences between the three study conditions (Mander et al, ). Furthermore, trajectories of alliance effects turned out similarly (Mander et al, ).…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Hence, the differences between mindfulness and PMR turned out in a more pronounced manner for therapists. In summary, it is important to note that in the main study, the primary outcomes on symptom reduction showed no significant differences between the three study conditions (Mander et al, ). Furthermore, trajectories of alliance effects turned out similarly (Mander et al, ).…”
Section: Discussionmentioning
confidence: 79%
“…The trial of our paper was registered at ClinicalTrials.gov (NTC02270073). Details on the original study protocol are published in Mander et al (), and the main results of the current study are published elsewhere (Mander et al, ). Potential participants were screened via clinical telephone interviews based on the SCID to assess anxiety or depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations